DNA methylation analysis explores the molecular basis of plasma cell-free DNA fragmentation - Yunyun An; Xin Zhao; Ziteng Zhang; Zhaohua Xia; Mengqi Yang; Li Ma; Yu Zhao; Gang Xu; Shunda Du; Xiang’an Wu; Shuowen Zhang; Xin Hong; et al. (Nature Communications, 2023)
Cell free DNA is produced through a non-random process. Here, the authors use orientation-aware fragmentation analysis to identify DNA methylation as a regulator of nuclease function.